KORELASI ANTARA LAJU ENDAP DARAH DENGAN DEFISIT NEUROLOGIS PADA STROKE HEMORAGIK - , Suryo Bantolo; , Prof. Dr. dr. Sri Sutarni, SpS(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background Hemorrhagic stroke is a devastating condition whose mortality rate is significantly high. Neurological worsening in hemorrhagic stroke could arise from primary injury and secondary injury. Secondary injury in hemorrhagic stroke assumed by the process of inflammation response. Previous studies stated that inflammation influences the neurological deficit that occurred. Hence, novel approach of management aimed to alleviate the inflammation. To measure level of inflammation level, several biomarker are used. Erythrocyte Sedimentation Rate (ESR) is one of inflammation biomarker that is expected can disclose magnitude of inflammation process that progressed in stroke hemorrhagic. This research would like to study the correlation of neurological deficits in hemorrhagic stroke patients and the level of ESR. Method This study used a cross sectional design with consecutive sampling technic. Each subject was asked to sign informed consent. The study was conducted on admission to the Dr. Sardjito hospital and all patients were receiving treatment for hemorrhagic stroke. Statistical analysis for each variable is using pearsonâs test for parametric and spearmanâs for non-parametric data. The results of bivariate analysis followed by multivariate analysis with linear regression. Result and discussion Correlation of Erythrocyte Sedimentation Rate and Neurological Deficits in Hemorrhagic Stroke Suryo Bantolo*, Sri Sutarni**, Abdul Gofir** *Resident of Neurology Departement FK-UGM/ Dr.Sardjito Hospital **Senior Staf of Neurology Departement FK-UGM/ Dr.Sardjito Hospital The study was conducted in June-August 2012 at Neurology deparment Dr Sardjito Hospital. Achieved total of 42 subjects, 22 men, 20 women. Based on statistical analysis, no significant correlation between erythrocyte sedimentation rate with neurological deficits which examined with Gadjah Mada Stroke Scale in patients with hemorrhagic stroke. This is possibly because the erythrocyte sedimentation rate examination performed at the onset of the attack, before the inflammatory reaction that occurs on the fifth day. There may also be due to a polymorphism in subjects that increased cytokine response does not occur. The weakness of this study is not examining the liver function where the synthesis of fibrinogen that affects erythrocyte sedimentation rate occurs. Conclusion In this study there was no correlation between erythrocyte sedimentation rate with neurological deficits were examined with Gadjah Mada Stroke Scale in patients with hemorrhagic stroke.